Peptide-Based Therapeutic Approaches for Treatment of the Polyglutamine Diseases - Takeuchi, Toshihide; Akiko Popiel, H.; Futaki, Shiroh; Wada, Keiji; Nagai, Yoshitaka (Current Medicinal Chemistry, 2014)
The polyglutamine (polyQ) diseases including Huntington’s disease and spinocerebellar ataxias are a group of inherited neurodegenerative diseases that are caused by an abnormal expansion of the polyQ stretch in disease-causative proteins. The expanded polyQ stretches are intrinsically unstable and are prone to form insoluble aggregates and inclusion bodies. Recent studies have revealed that the expanded polyQ proteins gain cytotoxicity during the aggregation process, which may possibly cause detrimental effects on a wide range of essential cellular functions leading to eventual neuronal degeneration. Based on the pathogenic mechanism of the polyQ diseases, several therapeutic approaches have been proposed to date. Among them, here we focus on peptide-based approaches that target either aggregate formation of the polyQ proteins or abnormal cellular processes induced by the expanded polyQ proteins. Although both approaches are effective in suppressing cytotoxicity of the abnormal polyQ proteins and the disease phenotypes of animal models, the former approach is more attractive since it targets the most upstream change occurring in the polyQ diseases, and is therefore expected to be effective against various downstream functional abnormalities in a broad range of polyQ diseases. One of the major current problems that must be overcome for development of peptide-based therapies of the polyQ diseases is the issue of brain delivery, which is also discussed in this article. We hope that in the near future effective therapies are developed, and bring hope to many patients suffering from the currently untreatable polyQ diseases.
Keywords: polyglutamine diseases